Characteristics of Profile Pin Variation in HDPE Friction Stir Welding to Mechanical Properties of Materials - Agus Wahyu Setiawan; Budi Darsono, Febri; Kriswanto; Ramadhani, Riski (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
Friction Stir Welding (FSW) is one of the Solid-State Welding processes, which joins materials below their melting point by continuously rubbing two workpieces together to generate heat. The FSW process heavily relies on the use of pin profiles, which play a crucial role in forming the weld joint, as they directly affect material flow in the weld zone and heat distribution during the welding process. This research aims to evaluate the mechanical properties of FSW joints made using different pin profile variations, in order to achieve high-quality welds. The study applies a descriptive statistical analysis approach, utilizing tensile testing, flexural testing, hardness testing, and macro photography. The material used in this research is High-Density Polyethylene (HDPE), with three types of pin profiles: triangular, threaded cylindrical, and grooved cylindrical. The welding parameters are kept constant: feed rate of 25 mm/min, spindle speed of 930 RPM, plunge depth of 3.84 mm, and tilt angle of 0°. The results show that the threaded pin profile produced the highest average values: hardness of 59.5 SHD, tensile strength of 11.5 MPa, and flexural strength of 22.4 MPa. In contrast, the grooved pin profile showed the lowest average values: hardness of 57.83 SHD, tensile strength of 4.99 MPa, and flexural strength of 4.22 MPa. The mechanical strength test results were influenced by weld defects observed through macro images. These weld defects significantly impacted the mechanical properties and demonstrated that pin profile geometry plays a vital role in heat generation through friction and in controlling the material flow dynamics, which directly determine the structural integrity and mechanical performance of the weld joint.